2014
DOI: 10.1111/jhq.12014
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Quality Improvement Throughput Measures at a High-Volume Community Emergency Department

Abstract: Despite an increase in patient census, the LWBS rate and door-to-doctor time decreased. This study of one solution to the issue of ED crowding demonstrates how a process redesign can lead to successful changes in throughput metrics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Others have reported that LWBS can be significantly improved by placement of a physician or mid-level provider (MLP) at triage. 19 , 21 , 22 These programs seem to usually, although not invariably, result in a statistically significant reduction in LWBS. 23 Similarly favorable impact on LWBS has been reported with the institution of a “fast track” area of the ED, at which location less-critical patients are seen.…”
Section: Discussionmentioning
confidence: 96%
“…Others have reported that LWBS can be significantly improved by placement of a physician or mid-level provider (MLP) at triage. 19 , 21 , 22 These programs seem to usually, although not invariably, result in a statistically significant reduction in LWBS. 23 Similarly favorable impact on LWBS has been reported with the institution of a “fast track” area of the ED, at which location less-critical patients are seen.…”
Section: Discussionmentioning
confidence: 96%
“…This practice has now changed and since ED operations performance can be significantly improved by placement of a physician or advanced practice provider at triage, the physician-out-front plan may be part of future operational (and tMD improvements). 19 , 26 , 27 …”
Section: Limitationsmentioning
confidence: 99%
“…Fortunately, there is evidence that focusing solely on tMD – while providing only a part of the overall picture – yields results of substantial operational importance. 26 …”
Section: Limitationsmentioning
confidence: 99%
“…As of January 2012, the annual reporting of LWBS rates as a quality metric is required by the Centers for Medicare and Medicaid Services [6]. LWBS may also represent a significant negative economic impact on hospitals in the form of lost revenue and exposure to increased risk [7]. To date, these authors have not yet found decisive data to demonstrate the extent of this cost or exposure.…”
Section: Introductionmentioning
confidence: 99%
“…LWBS has often been identified as a problem related to suboptimal ED efficiency. Approaches to decrease LWBS include placing a provider in triage, implementing nursing order protocols, streamlined communication between the ED/inpatient units, leasing mobile units to act as fast-track departments, and variations of direct bedding [6][7][8][9][10][11][12][13][14][15]. The provider in triage approach not only decreases LWBS but also increases ED throughput metrics especially in large urban hospitals [12].…”
Section: Introductionmentioning
confidence: 99%